2014
DOI: 10.1017/s1751731114001530
|View full text |Cite
|
Sign up to set email alerts
|

Variation in enteric methane emissions among cows on commercial dairy farms

Abstract: Methane (CH 4 ) emissions by dairy cows vary with feed intake and diet composition. Even when fed on the same diet at the same intake, however, variation between cows in CH 4 emissions can be substantial. The extent of variation in CH 4 emissions among dairy cows on commercial farms is unknown, but developments in methodology now permit quantification of CH 4 emissions by individual cows under commercial conditions. The aim of this research was to assess variation among cows in emissions of eructed CH 4 during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 18 publications
6
48
1
Order By: Relevance
“…Previous studies [18,21] have identified important explanatory variables describing CH 4 emissions per individual cow as being time of year, stage of lactation, time of day, and effect of farm. The following model was used to describe emissions from individual cows with the inclusion of explanatory variables for feeding system effects:…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies [18,21] have identified important explanatory variables describing CH 4 emissions per individual cow as being time of year, stage of lactation, time of day, and effect of farm. The following model was used to describe emissions from individual cows with the inclusion of explanatory variables for feeding system effects:…”
Section: Discussionmentioning
confidence: 99%
“…To do this, a fixed volume (2.7 L) of 1.0% CH 4 in nitrogen was released at two locations in the feed bin of the milking station, which were at the base of the trough and at the centre of the feed bin level with the sample tube. Release of CH 4 was replicated three times at each location, with the dilution factor being the mean ratio of six values of CH 4 concentrations in released and sampled gas [18]. Concentration of CH 4 in the air sampled followed a pattern of peaks and troughs demonstrating that a pulse release of CH 4 was eructated by the cow.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence indicating that daily CH 4 emission rates (g/day) of dairy cows varied considerably during lactation, but followed the variation curves of feed intake and milk production (Garnsworthy et al, 2012). Daily CH 4 emission rates also vary among cows on commercial farms (Bell et al, 2014). Therefore, further studies designed specially to compare the production capacity, rumen ecology and methanogenesis in dairy cows with different genetic merits (PIN or PLI) may be required to validate the results obtained in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, one challenge is to propose both feeding and breeding practices that can reduce methane emissions while competing less with human food (Dumont et al, 2014). Part of the solution lies in the genetic variability of methane emissions that has been evidenced in cattle (Bell et al, 2014) and sheep (Pinares-Patiño et al, 2013). Lower methane emissions could be achieved through indirect selection on correlated traits such as residual feed intake; reductions in methane emissions per cow of around 11% to 26% within 10 years are thus theoretically possible by selecting more efficient cows de Haas et al, 2011).…”
Section: Sparing Natural Resourcesmentioning
confidence: 99%